(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
ملخص يتناول هذا البحث تنظيم الأسواق وحماية المستهلك عن طريق ولاية الحسبة، وهي من أهم الولايات الشّرعية التي حرص النّظام الإسلامي في تاريخه الطويل على عقدها لناظر السّوق، تحت مسمّى"المحتسب"، الذي يُشترط فيه العلم والنّزاهة ومعرفة أحوال التّجار، لمحاربة الغش والتدليس والتطفيف في الكيل والميزان، حمايةً للمستهلك ومنعا من أكل أموال النّاس بالباطل، وهو ما عبّر عنه قانون حماية المستهلك وقمع الغش بمصطلح "حماية المصالح المادية والمعنوية للمستهلكين". لقد حاولت هذه الدراسة أن تجمع بين الجانب الشّرعي والقانوني في تنظيم الأسواق من خلال القوانين الناظمة لذلك، لاسيما قانون حماية المستهلك وقمع الغش 09-03، وقانون القواعد المحددة للممارسة التجارية 04-02. الكلمات الدالة: الحسبة، السوق، حماية المستهلك، الفقه الإسلامي، القانون الجزائري. Abstract: This research deals with the regulation of markets and consumer protection through the mandate of Hisba, one of the most important legal mandates that the Islamic regime in its long history held to the market supervisor, under the name "Al-Muhtaseb", which requires science, integrity and knowledge of merchants, to fight fraud, fraud and mitigation The balance is to protect the consumer and prevent the people from eating the people’s money in vain, as expressed in the Consumer Protection and Suppression of Fraud Law with the term "protecting the material and moral interests of consumers". This study has attempted to combine the legal and legal aspects of regulating markets through the laws governing it, especially the Consumer Protection and Fraud Suppression Act 09-03, and the Specific Rules of Business Practice 04-02. Key words: Hesba, the market, consumer protection, Islamic Fiqh, Algerian law